A sensitivity analysis for frictionless contact problems - Chen, Xian; Mori, Masahiko; Hisada, Toshiaki (Computer Assisted Methods in Engineering and Science, 1996)
A sensitivity analysis method for elasto-plastic contact problems with large deformation is developed based on two contact constraint methods, i.e., the Lagrange multiplier and penalty methods. Throughout the formulation the importance of using consistent contact stiffness in the sensitivity analysis is emphasized, and is demonstrated in a simple contact problem. Also a heat-transfer tube and plate contact system of heat exchanger used in PWR is analyzed as a real numerical example. The obtained sensitivities of residual stress resulting from the tube expansion process are discussed so as to provide implications for design improvement and quality control.